The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1086/656282
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Tuberculosis Screening for HIV‐Infected Patients Starting Antiretroviral Therapy in Durban, South Africa

Abstract: Background The World Health Organization (WHO) recommends cough as the trigger for tuberculosis (TB) screening in HIV-infected patients, with acid fast bacillus (AFB) smear as the initial diagnostic test. Our objective was to assess the yield and cost of a more intensive TB screening in HIV-infected patients starting antiretroviral therapy (ART) in Durban, South Africa. Methods We prospectively enrolled adults, regardless of TB signs/symptoms, undergoing pre-ART training from May ‘07–May ‘08. Following sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
126
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 18 publications
11
126
3
3
Order By: Relevance
“…Screening for this group requires high sensitivity to avoid missing cases, but in a resource-constrained setting, this must be balanced against the high costs resulting from a test combination with poor specificity. We found sputum microscopy had very poor sensitivity, consistent with other studies, 16,19,[23][24][25] as Xpert MTB/RIF 27 at US$17 per cartridge, 28 the cost to health services may be substantial, and the cost-effectiveness of a range of algorithms for different settings needs to be investigated. 90% of our culture-proven tuberculosis cases were smearnegative, and Xpert MTB/RIF has reported sensitivities from 43%-73% for smearnegative culture-positive tuberculosis from a single sputum sample.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Screening for this group requires high sensitivity to avoid missing cases, but in a resource-constrained setting, this must be balanced against the high costs resulting from a test combination with poor specificity. We found sputum microscopy had very poor sensitivity, consistent with other studies, 16,19,[23][24][25] as Xpert MTB/RIF 27 at US$17 per cartridge, 28 the cost to health services may be substantial, and the cost-effectiveness of a range of algorithms for different settings needs to be investigated. 90% of our culture-proven tuberculosis cases were smearnegative, and Xpert MTB/RIF has reported sensitivities from 43%-73% for smearnegative culture-positive tuberculosis from a single sputum sample.…”
Section: Discussionsupporting
confidence: 85%
“…In high prevalence settings systematic sputum culture for all patients prior to ART has also been suggested, but presents the same challenges of access. 12,16 In our study, most culture-positive patients started tuberculosis treatment based on clinical and radiological features prior to availability of culture results; even with liquid culture, the median time to tuberculosis treatment start based on a positive culture was 37 days.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…[14] For example, a study from Durban, SA, found that up to 22% of patients screened with sputum cultures prior to entering an ART programme had asymptomatic or subclinical TB. [23] However, despite modifying our screening protocol to include all HIV-infected patients regardless of symptoms, we did not find any subclinical or asymptomatic TB among HIV-infected patients participating in our study. This finding is likely to be influenced in part by a selection bias, as HIV-positive individuals in the community were not screened in a systematic way.…”
Section: Fig 1 Consort Study Diagram *Patients Temporarily Visitinmentioning
confidence: 61%
“…13 Consequently, this method fails to identify about 25-50% of the patients with TB, [14][15][16][17] and is even less sensitive in HIVpositive patients (9-57%). 17,18 More sensitive methods for diagnosis of TB are polymerase chain reaction (PCR) of the sputum, cultures on solid media (Lowenstein-Jensen or Middlebrook formulations), and liquid media. 13 The main disadvantages of these methods are their high cost (e.g., commercial PCR systems and liquid culture in automated systems) and the long duration of incubation needed to obtain positive culture and drug susceptibility results (culture on solid media), which make these techniques unsuitable for use in remote third world regions.…”
Section: Introductionmentioning
confidence: 99%